(untitled) (Ar Rehla: Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2023)
Abstract: The Ministry of Tourism and Creative Economy has identified halal tourism as a significant area of focus. The slope of Mount Wilis possesses the potential to emerge as a tourism attraction that caters to the needs and preferences of Muslim travelers. The slopes of Mount Wilis possess significant potential to serve as an emblematic halal tourist destination in western East Java, thereby contributing to the development of tourism in the region. The present study employed a qualitative research methodology. The data was obtained via interviews conducted with tourism stakeholders in the regions of Watu Rumpuk and Taman Gligi. Furthermore, the process of data triangulation involved the utilization of observation. The findings show that the tourism industry in the slope of Mount Wilis exhibits promising prospects for the development of halal tourism. This paper proposes a strategic approach to foster the growth of halal tourism in the regions of Watu Rumpuk and Taman Gligi through collaborative efforts among many stakeholders. The key areas of focus for this collaboration include enhancing the quality of services, preserving the natural environment, improving communication channels, and ensuring accessibility for halal tourism. Keywords: Potential; Strategy; Halal Tourism; Mount Wilis Abstrak: Kementerian Pariwisata dan Ekonomi Kreatif telah menjadikan wisata halal sebagai fokus pengembangan sector pariwisata yang potensial. Lereng Gunung Wilis memiliki potensi untuk menjadi daya tarik pariwisata yang memenuhi kebutuhan dan preferensi wisatawan Muslim. Lereng Gunung Wilis memiliki potensi baik untuk dikembangkan menjadi destinasi wisata halal yang ikonik di wilayah barat Jawa Timur, sehingga dapat berkontribusi pada pengembangan pariwisata di wilayah tersebut. Penelitian ini menggunakan metodologi penelitian kualitatif. Data diperoleh melalui wawancara yang dilakukan dengan pemangku kepentingan pariwisata di wilayah Watu Rumpuk dan Taman Gligi. Selain itu, proses triangulasi data melibatkan penggunaan observasi. Temuan menunjukkan bahwa industri pariwisata di lereng Gunung Wilis menunjukkan prospek yang menjanjikan untuk pengembangan pariwisata halal. Makalah ini mengusulkan pendekatan strategis untuk memajukan pertumbuhan pariwisata halal di wilayah Watu Rumpuk dan Taman Gligi melalui upaya kolaboratif antara banyak pemangku kepentingan. Adapun fokus kerjasama ini mencakup peningkatan kualitas layanan, pelestarian lingkungan alam, perbaikan saluran komunikasi, dan memastikan aksesibilitas pariwisata halal. Kata Kunci: Potensi; Strategi; Pariwisata Halal; Gunung Wilis